Pressure, Temperature and Dwell Time Effects on Fatigue Life in 304 Stainless Steel Using a R5-based Mechanistic Fatigue Model. (2016) - Erinosho, T.O.; Li, P.; Truman, C.E.; Smith, D.J.
Abstract: This paper aims to evaluate the effects of pressure, temperature, pipe wall thickness and dwell time on fatigue life in 304 stainless steel. For a given dwell time and temperature-internal pressure combination, fatigue life is calculated using the mechanistic fatigue model (MFM) presented. In addition, the influence of pipe wall thickness is also examined. The MFM uses Tresca strain range for initiation and Rankine strain range to account for crack growth rate up to a crack limiting length. The results showed that fatigue life was generally lower for a given load combination in the thinner pipe considered given its smaller surface area compared to the thicker pipe. This led to higher plastic strains and consequently, faster crack growth rates. Also, dwell time influences fatigue life with longer dwell times found to be more damaging. However, the influence of dwell time is tightly coupled with pipe wall thickness as it determines the nature of the thermal gradients developed.